Systemic aspects of R&D policy subsidies for R&D collaborations and their effects on private R&D. Issue 2 (17th February 2016) - Engel, Dirk; Rothgang, Michael; Eckl, Verena
Abstract: This paper analyses how context- and time-dependent factors determine the impact of R&D subsidies on firm behaviour with respect to private R&D expenditures. Based on German R&D survey data, we combine propensity score matching with a difference-in-difference estimator in order to measure the causal influence of public direct R&D project funding on firm behaviour. Our results indicate that (i) repeated participation in R&D projects on average leads to a higher increase in R&D expenditures than once-off funding; (ii) the aggregate effect of R&D funding on R&D expenditures of business firms is somewhat higher for business–business collaboration projects than for science–business collaboration projects; (iii) R&D expenditures of business firms that cooperate with science show a higher share of external R&D spending. Results of one particular cluster programme indicate that at least the short-term development of R&D does not so much depend on which programme direct R&D project funding is applied to.